2020
DOI: 10.7759/cureus.8058
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Mobilization and Functional Constipation in Stroke Survivors: A Randomized, Controlled, Double-Blind, Clinical Trial

Abstract: Open Access Original Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Gangguan pergerakan atau mobilitas dapat mempengaruhi kemampuan klien terhadap keinginan buang air besar. Akibatnya, klien mengalami konstipasi atau fecal inkontinentia yang disebabkan karena sangat berkurangnya fungsi dari sfingter ani (Baran & Ates, 2019;Neto & Borges, 2020).…”
Section: Pembahasanunclassified
“…Gangguan pergerakan atau mobilitas dapat mempengaruhi kemampuan klien terhadap keinginan buang air besar. Akibatnya, klien mengalami konstipasi atau fecal inkontinentia yang disebabkan karena sangat berkurangnya fungsi dari sfingter ani (Baran & Ates, 2019;Neto & Borges, 2020).…”
Section: Pembahasanunclassified
“…Some studies have demonstrated an improvement in flexibility and visceral function after manual treatment, which can impact on peripheral sensitization and interoception. Still's technique applied to the kidney generates increased renal mobility and decreased back pain in volunteers with low back pain [ 60 ]; mobilization of the sigmoid colon of asymptomatic volunteers generates hypoalgesia at the L1 level and the OMT, including visceral treatment, improves intestinal constipation, including stroke survivors [ 64 - 66 ].…”
Section: Reviewmentioning
confidence: 99%
“…Functional chronic bowel constipation is a motility disorder of great relevance and prevalence worldwide 1 . According to the Rome III Consensus, it is defined as the presence, in the previous six months, of two or more of the following criteria: less than three bowel movements per week, effort to evacuate hard or fragmented stools, obstruction or anorectal blockage sensation and use manual maneuvers to facilitate evacuations 2 .…”
Section: Introductionmentioning
confidence: 99%